Fear, family and the placing of emotion: Black women's responses to a breast cancer awareness intervention. (December 2017) - Brown, Tim; Dyck, Isabel; Greenhough, Beth; Raven-Ellison, Menah; Dembinsky, Melanie; Ornstein, Mark; Duffy, Stephen W.
Abstract: This paper is based upon findings from the qualitative element of a mixed-methods study on the response of Black women aged 25–50 to a public health intervention related to breast cancer. The focus groups were conducted in the London Borough of Hackney, UK between 2013 and 2016, and were part of an evaluation of the effectiveness of a breast awareness DVD. While the content of the DVD was generally well-received by the participants, the focus group discussions revealed a complex and, at times, contradictory response to the women's construction as an 'at risk' community. As the paper highlights, for many of the women, breast cancer remains a disease of whiteness and the information provided in the DVD prompted a range of emotional responses; from anxiety and fear to a desire to become more knowledgeable and active in the promotion of self-care. As the paper argues, of particular importance to the women was the need to feel a much stronger emotional connection to the information presented in the DVD. The paper concludes by arguing that placing greater emphasis on feeling and emotion is an important dimension of future research in this area. Highlights: Breast cancer remains a 'white woman's disease' for many Black women. Representations of breast cancer as 'aggressive' promote anxiety and fear. Emotion is important to Black women's embodiment of breast cancer risk.